Ultrastability and color-tunability of CsPb(Br/I)3 nanocrystals in P–Si–Zn glass for white LEDs. Issue 87 (20th September 2018) - Jiang, Jutao; Shao, Guangzhan; Zhang, Zelong; Ding, Ling; Zhang, Huiling; Liu, Jianming; Chen, Zhaoping; Xiang, Weidong; Liang, Xiaojuan
Abstract : A series of CsPbBr x I3− x NC glasses, showing tunable emission (523–693 nm) controlled by different ratios of Br − and I −, were successfully prepared. Abstract : A series of CsPbBr x I3− x NC glasses, showing tunable emission (523–693 nm) controlled by different ratios of Br − and I −, were successfully prepared. The CsPbBr x I3− x NC glasses exhibited excellent optical properties and outstanding stability towards ambient conditions, water and heat.